Pengaruh Model Pembelajaran PjBL Berbantuan Media Wordwall Terhadap Aktivitas dan Hasil Belajar IPA Siswa Kelas V SD Inpres Bontoala I Kabupaten Gowa - Hasrita, Hasrita; Nurlina, Nurlina; Ma’ruf, Ma’ruf (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of the Project-Based Learning (PjBL) model assisted by Wordwall media on learning activities, to analyze its influence on science learning outcomes, and to analyze its influence on both learning activities and science learning outcomes of fifth-grade students at SD Inpres Bontoala I, Gowa Regency. This research is an experimental study. The independent variable is the PjBL learning model assisted by Wordwall, while the dependent variables are students’ learning activities and learning outcomes. The research design used is a non-equivalent control group design. The sample consisted of 35 students from class V.A as the experimental group and 35 students from class V.B as the control group. Data collection techniques were carried out through observation, questionnaires, and tests. Hypothesis testing was conducted using SPSS 26. The results showed a significance value (Sig.) of 0.000 < 0.05, indicating a significant difference between the average learning outcomes of the experimental group using the PjBL model assisted by Wordwall and the control group using conventional methods. In other words, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Thus, it can be concluded that the PjBL model assisted by Wordwall media significantly improves student learning activities. The activities of the experimental group students were categorized as high compared to the control group. Similarly, the learning outcomes showed that the average post-test scores were higher than the pre-test scores, indicating that the use of the PjBL model assisted by Wordwall media has an influence on the learning activities and outcomes of fifth-grade students at SD Inpres Bontoala I, Gowa Regency.